Numerical Investigation on Hydrodynamic Performance of an OWC Wave Energy Device in the Stepped Bottom - Ning, De-Zhi; Ke, Song; Mayon, Robert; Zhang, Chongwei (Frontiers in Energy Research, 2019)
The efficiency response of an oscillating water column (OWC) wave energy converter is analysed by adopting a numerical approach and using various stepped bottom configurations for the seabed. A two-dimensional, fully non-linear higher-order boundary element method (HOBEM) model is developed to simulate the hydrodynamic characteristics and fluid structure interaction for a fixed OWC located in a numerical wave flume. A number of model tests are conducted for various regular incident wave conditions by modifying the wave amplitudes and wavelengths. The measured free surface elevation at the chamber centre and the oscillatory air pressure generated by the fluctuating free surface within the chamber are recorded. The hydrodynamic efficiency of the OWC is determined using these parameters. The simulation results are validated by comparing against previously published experimental and numerical data. Good agreement is observed in both cases. The geometric dimensions of the step are modified by altering the step height and step length. Furthermore, by altering the step length, the location of the front face of the step relative to the front wall of the OWC is adjusted. Therefore, the positional significance of the step can also be analysed in terms of its relative location to the OWC chamber and to the flow field development. It is shown that the geometry of the step and the position of the vertical face of the step relative to the OWC influences the hydrodynamic efficiency. The research demonstrates that by optimising the step geometry and position for a given wave condition a higher operational efficiency can be achieved.